Livros didáticos de língua portuguesa: o ensino de gêneros textuais - Madeira, Mônica Saad (2012)
This work analyzes the inclusion and teaching approach of textual genres in Portuguese language coursebooks in high school. It aims at investigating the most used genres in the analyzed materials, the order that they are presented and taught. In other words, the purpose of teaching them to the students, identifying similarities and differences in the way they are exposed to the students. This study will contribute to the fields of linguistics, applied linguistics and education. The approach of relevant questions to the language and to the reading demands of the researcher an interdisciplinary perspective. This research proposes a reflection concerning issues that involve an inspired development of the reader in school environment. The School has a double challenge: turn an occasional reader into a captive one, with different text genres, aware of the permanent condition of being unfinished. So, an eternal learner; the second, motivated by the first, consists of starting and ensure the passage of the state of an inexperienced student-reader, ineffective, to the status of a critical an conscious one.